Strategic management : Competitiveness and globalization, concepts and cases - Hitt, Michael A.; Ireland, R. Duane; Hoskisson, Robert E. (Boston Cengage Learning, 2017)
Examine strategic management with the market-leading text that sets the standard for the most intellectually rich, practical analysis of strategic management.
Keywords: Quản trị kinh doanh